Effect of forward speed on field performance of power tiller with and without operator's seat - TIWARI, P S; VARSHNEY, A C (The Indian Journal of Agricultural Sciences, 2014)
A 10.5 kW rotary type-power tiller fitted with operator's seat was field evaluated at 6 levels of forward speed for rotatilling operation under heavy soils of Bhopal region and its performance was compared with that of power tiller without operator's seat. Effective field capacities of power tiller rotavator with operator's seat increased from 0.055 to 0.213 ha/hr when the forward speed increased from 1.04 to 4.14 km/hr. However, without operator's seat the effective fieldcapacities were 0.057-0.220 ha/hr for forward speed of 1.06-4.16 km/hr. Fuel consumption of power tiller with operator's seat ranged between 0.97 and 1.24 litres/hr for the forward speed of 1.04-3.06 km/hr at three-fourths of rated engine speed (1500 rpm) and 1.23-1.68 litreshr for the forward speed of 1.39-4.14 km/hr at rated engine speed (2 000 rpm). Without operator's seat fuel consumption of power tiller was 0.95-1.22 litres/hr at the forward speed of 1.06-3.09 km/hr at three fourths of rated engine speed (1 500 rpm) and 1.20-1.60 litres/hr at the forward speed of 1.42-4. 16 km/hr at rated engine speed (2 000 rpm). Depth of operation with and without operator's seat decreased from 12.0 to 7.8 cm and 11.0 to 7.0 cm with the increase in forward speed from 1.04 to 4.14 km/hr and 1.06 to 4.16 km/hr respectively. Operating cost of powertiller with and without operator's seat decreased from Rs 1 005.80 to 301.22 and Rs 966.14 to 287 .14/ha with increase inforward speed from 1.04 to 4.14 km/hr and 1.06 to 4.14 km/hr respectively. No significant reduction was observed in fieldcapacity with operator's,seat. Fuel consumption and depth of operation were affected with operator's seat at 5% level ofsignificance, while effect of operator's seat on cost of operation was significant at 1 % level. Different levels of forward speed affected the above parameters significantly at 1 % level.